2012
DOI: 10.1055/s-0031-1291441
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics after endoscopic submucosal injection of epinephrine in a porcine model

Abstract: Endoscopic submucosal injection of epinephrine is associated with changes in systemic hemodynamic parameters, especially when performed in the esophagus, and the procedure might therefore induce harmful side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the present study, a decrease in DBP was not associated with tachycardia, which may be because of concurrent fentanyl use at the time of anesthesia induction. In another animal study (Schlag et al, 2012), the hemodynamic effects of sub-mucosal injection of two volumes of adrenaline (1:10,000) into different parts of the upper gastrointestinal track during endoscopy in pigs were assessed. The results of this study showed significant hemodynamic changes after endoscopic submucosal injection of adrenaline especially in the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a decrease in DBP was not associated with tachycardia, which may be because of concurrent fentanyl use at the time of anesthesia induction. In another animal study (Schlag et al, 2012), the hemodynamic effects of sub-mucosal injection of two volumes of adrenaline (1:10,000) into different parts of the upper gastrointestinal track during endoscopy in pigs were assessed. The results of this study showed significant hemodynamic changes after endoscopic submucosal injection of adrenaline especially in the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…18,27 Even if infrequent, adverse cardiac events have been described after a high volume (30 mL) of epinephrine for treatment of a bleeding Mallory-Weiss tear. 28,29 Sclerosants Sclerosants agents, such as polidocanol, ethanol, and ethanolamine, induce local inflammation and subsequent fibrosis, obliterating the lumen of the vessel. The technique is similar to that used for epinephrine, but volumes are much smaller (usually a maximum of 1 mL, divided in 0.1-0.3 mL aliquots per injection at 3-4 sites around or into the visible vessel) due to the potential risk of ulceration, necrosis, and perforation described for those agents.…”
Section: Epinephrinementioning
confidence: 99%